THE ACCOUNTING OF LOGISTICS COSTS FOR THE ORGANIZATION AND MANAGEMENT OF PRODUCTION IN THE ACCOUNTING AND ANALYTICAL SUPPORT OF THE MICROLOGISTICS SYSTEM - Plysa, Volodymyr; Plysa, Zoriana; Rudnitski, Yaroslav (Socio-economic relations in the digital society, 2022)
The purpose of the article is to find out the peculiarities of the organization of accounting of logistics costs for the organization and management of production in the accounting and analytical support of the micrologistics system. The interpretation of the concept of "accounting and analytical support of the micrologistics system" has been clarified, under which it is proposed to understand the formation, collection, analytical and synthetic processing, accumulation and transfer of justified and relevant accounting and analytical information generated using accounting and economic analysis methods for making management decisions related to a single flow process of moving materials and information through the chain from the producer to the consumer. A general model of accounting and analytical support for the micrologistics system is proposed. For the purposes of the conducted research, it is suggested that logistics costs should be understood as all costs of the logistics system associated with a single flow process of moving materials and information through the chain from the producer to the consumer. The classification of logistics costs for the organization and management of production according to a functional feature is proposed, which makes it possible to evaluate systematically their absolute values, solve operational problems regarding the justification of the optimal size of these costs, using an array of operational accounting information carry out an analysis of the structure of logistics costs and organize an effective condition control system expenses related to logistics operations. To increase the level of responsiveness to the behaviour of logistics costs for the organization and management of production, it is proposed to introduce seven analytical accounts to the synthetic account 91 "General production costs" ("Logistics costs for the organization of technological support of the production process", "Logistics costs for equipment maintenance", "Logistics costs for replacing equipment", "Logistics costs for technical assurance of product quality (works, services)", "Logistics costs for drawing up production schedules", "Logistics costs for intra-production movement", "Logistics costs for disposal of production waste"), which will be grouped into a separate subaccount 911 "Logistics costs for the organization and management of production". This information array, according to the authors, will become the basis of the operational analysis of logistics costs for the organization and management of production in the accounting and analytical support of the micrologistics system, which in turn will improve the management of streams in the logistics chain.
Keywords: analytical account; accounting; logistics; enterprise logistics; micro-logistics system; logistics costs for the organization and management of production; accounting and analytical support; sub-account